2013
DOI: 10.1212/wnl.0b013e3182a1aa3e
|View full text |Cite
|
Sign up to set email alerts
|

Temporal reorganization to overcome monocular demyelination

Abstract: Delayed latencies in the fellow eyes may reflect adaptive mechanisms at the cortical level that improve binocular integration over time to adjust for the damage incurred. These data provide a unique demonstration of temporal reorganization that compensates for delayed transmittal of visual information to the cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 34 publications
(31 reference statements)
2
39
1
1
Order By: Relevance
“…Latency of the fellow eye in HR group also demonstrated tendency to increase, although not to the same extent as patients in the MS group. Delayed latency in fellow eyes of ON patients has been suggested as a part of central adaptive mechanism at the cortical level to compensate for delayed cortical visual input from ON eyes (Raz et al, 2013). The fact that fellow eyes of LR subgroup in this study did not show significant latency delay argues against this suggestion.…”
Section: Discussioncontrasting
confidence: 53%
“…Latency of the fellow eye in HR group also demonstrated tendency to increase, although not to the same extent as patients in the MS group. Delayed latency in fellow eyes of ON patients has been suggested as a part of central adaptive mechanism at the cortical level to compensate for delayed cortical visual input from ON eyes (Raz et al, 2013). The fact that fellow eyes of LR subgroup in this study did not show significant latency delay argues against this suggestion.…”
Section: Discussioncontrasting
confidence: 53%
“…This test was designed to test the hypothesis that due to demyelination at the affected nerve, information from the two eyes will reach the cortex at different time points impairing binocular integration in time. Testing a group of recovered ON patients (1-2.5 years following the attack), we have shown that while most patients had intact performance levels in a standard static stereo task; performance on the time-constrained stereo task was impaired in most cases 10 .…”
Section: Dynamic Visual Tests May Be Used As Markers Of Demyelinationmentioning
confidence: 96%
“…The reason why VEP incongruities are observed in the asymptomatic eye remains debated. Three main hypotheses have been discussed in the literature: (1) VEPs are able to detect subclinical abnormalities of the optic nerve due to previous injury or (2) due to retrograde axonal degeneration9 or (3) its latency delay results from a visual compensation in the attempt to coordinate information arriving to the occipital cortex 10…”
Section: Visual Evoked Potentialsmentioning
confidence: 99%